Livedo Racemosa – The Pathophysiology of Decompression-Associated Cutis Marmorata and Right/Left Shunt - Hartig, Frank; Reider, Norbert; Sojer, Martin; Hammer, Alexander; Ploner, Thomas; Muth, Claus-Martin; Tilg, Herbert; Köhler, Andrea (Frontiers in Physiology, 2020)
Decompression sickness and arterial gas embolism, collectively known as decompression illness (DCI), are serious medical conditions that can result from compressed gas diving. DCI can present with a wide range of physiologic and neurologic symptoms. In diving medicine skin manifestations are usually described in general as cutis marmorata (CM). Mainly in the Anglo-American literature the terms cutis marmorata, livedo reticularis and livedo racemosa are used likewise, but actually describe pathophysiologically different phenomena. CM is a synonym for livedo reticularis (LR), which is a physiological and benign, livid circular discoloration with a net-like, symmetric, reversible and uniform pattern. The decompression associated skin discolorations, however, correspond to the pathological, irregular, broken netlike pattern of livedo racemosa (LRC). Unlike in diving medicine, in clinical medicine/dermatology the pathology of livedo racemosa is well described as a thrombotic/embolic occlusion of arteries. This concept of arterial occlusion suggests that the decompression associated livedo racemosa may be also caused by arterial gas embolism. Recent studies have shown a high correlation of cardiac Right/Left-shunts with arterial gas embolism and skin bends in divers with unexplained DCI. To further investigate this hypothesis, a retrospective analysis was undertaken in a population of Austrian, Swiss and German divers. The R/L-shunt screening results of 18 divers who suffered from an unexplained decompression incident (DCI) and presented with livedo racemosa were retrospectively analyzed. All of the divers were diagnosed with a R/L-shunt, 83% with a cardiac shunt (PFO/ASD) and 17% with a non-cardiac shunt. We therefore not only confirm this hypothesis, but when using appropriate echocardiographic techniques even found a 100% match between skin lesions and R/L-shunt. In conclusion, in diving medicine the term cutis marmorata/livedo reticularis is used incorrectly for describing the actual pathology of livedo racemosa. Moreover, this pathology could be a good explanation for the high correlation of livedo racemosa with cardiac and non-cardiac right/left-shunts in divers without omission of decompression procedures.